Factors Affecting Students' Intentions to Use the University's E-Payment System - Hersatoto Listiyono; Sunardi Sunardi; Sugiyamto Sugiyamto; Agus Prasetyo Utomo (Scientific Journal of Informatics, 2023)
Purpose: Most universities prioritize online payment administration because_of_advances_in_information_and communicatio_ technologies, especially for online_banking transactions. Benefits from online banking services such as  transactions via Internet banking are very convenient compared to traditional payment methods.  On other side is traditional payment methods transactions must queue and come directly to the bank. This study was done to find out what factors in Semarang City affected the adoption of university E-PS as online banking.Methods: 123 students have participated in this research. Six charactersitics were considered in a new study model that examinated how students’ intention to use E-PS was affected: convinience, perceived usefullness, risks, perceived trust and reputation. To validate the reearch model, the structural equation model approach using PLS-SEM was apllied.Result: The empirical result showed that perceived convinience, perceived usefullness and trust had e significan positive relationship with students’ intention to use the University’s E-PS.  The empirical results showed that perceived convenience, perceived usefullness, and trust had a significant_positivee_relationshipp_withhstudents’ intentions_to_use the E-PS university. Perceived convinience was also found to have a positive and significan effect on the perceived usefullness of students using E-PS. However, the perceived risks showed a non-significan negative relationship with tudents’ intentions to use E-PS.Novelty: While previous studies have explored the intentions to se E=PS. This research contributes the literature by invetigating the specific factors that influence the adoption of E-PS in the context of tertiary institutions. Additionally, this research provides empirical evidence on the relationhip between perceived convinience and perceived convience and perceived usefullness of using E-PS in univerities. Overall, this research offers a new perspective on the adoption of E-PS in tertiary institutions and contributes to the development of strategies to improve the adoption and use E-PS in universities.